Sosialisasi Penggunaan Media Sosial Secara Bijak Berdasarkan Undang-Undang Ite di Desa Sungai Ulak - Satria, Deni; Chandra, Febrian (Vox Populi: Jurnal Umum Pengabdian Kepada Masyarakat, 2024)
The advancement of information and communication technology has brought numerous benefits to society, particularly in facilitating access to information and communication. However, improper use of social media can lead to various negative impacts, such as the spread of hoaxes, defamation, and copyright infringement. This community service activity aims to provide an understanding to the Youtubers community in Sungai Ulak Village about the importance of using social media wisely in accordance with the Electronic Information and Transactions Law (UU ITE). The method used includes legal socialization and counseling with a juridical-empirical approach. The results of this activity indicate that participants gained a better understanding of social media ethics, related legal regulations, and ways to avoid legal violations. Through this activity, it is expected that the Youtubers community in Sungai Ulak Village can create more educational, positive, and legally compliant content.